Genetic diversity of the human immunodeficiency virus of type 1 in Gabonese transfusional settings - Christian Mangala; Joseph Fokam; Denis Maulot-Bangola; Olivier Rebienot-Pellegrin; Thérèse Nkoa (BMC Infectious Diseases, 2023)
Abstract Background The high endemicity of transfusion-transmissible infections (TTIs) in sub-Saharan Africa is a real public health problem. To reduce the risk of HIV transmission through blood donation, the NBTC of Gabon has launched in recent years a reorganization of its blood transfusion system. This study aims to characterize the molecular strains of HIV-1 circulating in donors and to estimate the risk of viral transmission. Materials and methods A cross-sectional study was carried out during the period from August 2020 to August 2021 among 381 donors who had agreed to donate blood at the National Blood Transfusion Center (NBTC). Viral load was determined by Abbott Real-Time (Abbott m2000®, Abbott) and sequencing by the Sanger method (ABI 3500 Hitachi®). The phylogenetic tree was constructed by MEGA X software. Data were checked, entered, and analyzed using SPSS version 21.0 software, with p ≤ 0.05 considered statistically significant. Results A total of 381 donors were enrolled in the study. Among the 359 seronegative donors, five (5) seronegative donors were detected positive for HIV-1 using Real-Time PCR. The residual risk was 648 per 1,000,000 donations. The prevalence of residual infection was 1.4% [0,01; 0,03]. Sixteen (16) samples were sequenced. The strains obtained were CRF02_AG (50%), subtype A1 (18.8%), subtype G (12.5%), CRF45_cpx (12.5%) and subtype F2 (6.2%). Six sequences clustered with A1, G, CRF02_AG, and CRF45_cpx subtypes. Conclusion The residual risk of HIV-1 transmission by blood transfusion remains a concern in the Gabonese transfusional settings. A policy based on improving the current screening strategy would involve the implementation of the nucleic acid test (NAT) in order to optimize the safety of the donation by detecting the HIV-1 subtypes in circulation in the donors.